EFFECTS OF DIETARY STARCH REPLACEMENT WITH SUGAR ON LACTATION PERFORMANCE OF NILI RAVI BUFFALOES - Hina Tahir; Saima Naveed; Nisar Ahmad; Muhammad Asim Tausif; Burhan E Azam; Sundas Qamar; Saba Anwar; Abdul Jabbar; Muneer Ahmad Khan; Muhammad Imran; Muhammad Naveed-ul- Haque (Journal of Animal and Plant Sciences, 2025)
Feeding high starch diet is a common practice to increase milk production and similarly feeding sugars helps in improving milk fats. However, the extent to which trade-off between dietary starch and sugar content is possible for optimal milk production and fats is not fully explored in lactating Nili Ravi buffaloes. Twelve multiparous early-lactating Nili Ravi buffaloes (52 ± 37 d in milk, mean ±SD) received 3 treatments in a 3 × 3 Latin square design and each period consisted of 28 d. The dietary treatments contained starch and sugars in the following manner: 1) 28.7% starch, 2.61% sugar; 2) 25.9 % starch, 4.29% sugar; 3) 22.9% starch, 5.73% sugar on DM basis. All dietary treatments were iso-nitrogenous. Replacing dietary starch with sugar increased milk fat content, milk fat yield and 4% fat-corrected milk (FCM) linearly by 7.29, 13.8 and 11.9% respectively, however, milk yield was not affected by treatments. Similarly, energy-corrected milk (ECM) was also increased by 10.3% by the replacement of dietary starch with sugar. Body weight increased by 2% linearly, whereas, the body condition score remained unaffected as sugar replaced starch. There was a linear increase in plasma cholesterol concentrations, whereas plasma urea nitrogen, glucose, and triglyceride concentrations remained unaffected by increasing sugar. The marginal efficiency of NEL consumed for milk yield, 4% FCM and ECM increased linearly with increasing sugar. Feeding diets containing 22.9% starch and 5.37% sugar increased milk fat content, fat yield, and body weight of Nili Ravi buffalo without impacting on milk production and blood metabolites. Using sugar as a substitute for starch could be a practical option for producers without negatively impacting production.
Keywords: Buffaloes; milk production; grain starch